2022
DOI: 10.3390/cancers14174287
|View full text |Cite
|
Sign up to set email alerts
|

The Immune Landscape of Papillary Thyroid Cancer in the Context of Autoimmune Thyroiditis

Abstract: Papillary thyroid cancer (PTC) often co-occurs with Hashimoto’s thyroiditis, an association that has long been reported in clinical studies, remaining controversial. Experimental evidence has recently shown that pre-existing thyroiditis has a beneficial effect on PTC growth and progression by a distinctive expansion of effector memory CD8 T cells. Although the link between inflammation and PTC might involve different components of the immune system, a deep characterization of them which includes T cells, B cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 188 publications
0
9
0
Order By: Relevance
“…The relationship between AIT and TC has been the focus of considerable research aimed at determining the potential impact of thyroid autoimmunity on the clinical outcome of TC [ 26 , 27 ]. It is indicated that chronic inflammation in HT patients may provide a mutagenic environment through the contribution of intratumoural T and B lymphocytes to the evolution of TC [ 26 , 27 ]. According to various authors, the prevalence of thyroid nodules in children with AIT ranges from 12.2% to 31.5% [ 1 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between AIT and TC has been the focus of considerable research aimed at determining the potential impact of thyroid autoimmunity on the clinical outcome of TC [ 26 , 27 ]. It is indicated that chronic inflammation in HT patients may provide a mutagenic environment through the contribution of intratumoural T and B lymphocytes to the evolution of TC [ 26 , 27 ]. According to various authors, the prevalence of thyroid nodules in children with AIT ranges from 12.2% to 31.5% [ 1 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In their vicinity, high endothelial venules (HEVs) are present, enabling lymphocyte entrance into TLS [35]. TLS form under conditions of chronic inflammation and antigenic persistence, such as different solid cancer types, including not only melanoma, colorectal, lung, breast, ovarian, gastric, and so on [36–38], but also in autoimmune diseases like rheumatoid arthritis [39] and Hashimoto's thyroiditis [40]. TLS vary between and within different diseases, where they appear at distinct maturation stages, ranging from lymphoid aggregates to highly organized structures with germinal centers [2,41,42,43 ▪ ,44,45].…”
Section: Tertiary Lymphoid Structures In Cancer Immunologymentioning
confidence: 99%
“…The inability to incorporate all the relevant information that is collected during the evaluation of patients is evident in those who have FTC and are still not cured, even where management decisions are made through a multidisciplinary team. The use of artificial intelligence (AI) in healthcare has led to an improvement in the accuracy of diagnosis and decision-making during the management of benign and malignant disease [ 179 , 229 ].…”
Section: Artificial Intelligence and Management Of Ftcmentioning
confidence: 99%
“…Artificial intelligence relies on advanced computing to make decisions based on the information obtained from multiple sources [ 230 , 231 , 232 ]. Artificial neural network (ANN) and convolutional neural network (CNN) are examples of AI, which vary based on the number of inputs and hidden layers that are involved before a decision is reached [ 183 , 229 , 233 ] ( Figure 3 ).…”
Section: Artificial Intelligence and Management Of Ftcmentioning
confidence: 99%